The Pengaruh Pendidikan Kesehatan melalui Instagram terhadap Pengetahuan dan Sikap Pencegahan Anemia pada Remaja Putri - Pramudyta, Nabila Anggun Pramudyta; safitri, maya safitri; Pramesti, Pramesti Dewi (Jurnal Kesehatan, 2024)
Anemia is a worldwide health issue, and Indonesia is no exception. The understanding of adolescents about anemia can be improved through health education. Instagram is an appropriate social media platform to disseminate health information. This research aims to determine the effect of health education through Instagram on the knowledge and attitude of anemia prevention among female adolescents at SMK N 1 Bojongsari. This research applied a pre-experimental design involving one group with  pretest and posttest.  The population included in this research were 213 female adolescents from class X at SMK N 1 Bojongsari, Purbalingga in the 2023/2024 academic year who experienced from anemia and had an Instagram account. The students were selected using  total sampling technique. Knowledge and attitude questionnaire concerning the prevention of anemia was implemented in this study. After filling out the pretest questionnaire, respondents received health education for one week. After that, a posttest questionnaire was filled out. The results revealed that the majority of respondents had good knowledge at pretest, with 116 respondents (56.3%), and this number increased to 145 respondents (70.4%) at posttest. Respondents' attitudes were mostly positive at pretest, with 169 respondents (82%), and increased to 191 respondents (92.7%) at posttest. Wilcoxon statistical test results showed a p-value of 0.001, indicating that health education through Instagram has an effect on the knowledge and attitudes of female adolescents at SMK N 1 Bojongsari regarding anemia prevention. Therefore, it is recommended to implement health education through social media to improve the knowledge and attitudes in order to prevent anaemia.  Keywords: anemia prevention, attitude, health education, instagram, knowledge